2015
DOI: 10.1136/bmjopen-2015-008924
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ventilator-associated pneumonia in Australasian intensive care units: use of a consensus-developed clinical surveillance checklist in a multisite prospective audit

Doug Elliott,
Rosalind Elliott,
Anthony Burrell
et al.

Abstract: ObjectivesWith disagreements on diagnostic criteria for ventilator-associated pneumonia (VAP) hampering efforts to monitor incidence and implement preventative strategies, the study objectives were to develop a checklist for clinical surveillance of VAP, and conduct an audit in Australian/New Zealand intensive care units (ICUs) using the checklist.SettingOnline survey software was used for checklist development. The prospective audit using the checklist was conducted in 10 ICUs in Australia and New Zealand.Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 32 publications
7
24
1
9
Order By: Relevance
“…1 VAP is defined as pneumonia occurring 48 h following endotracheal intubation with the ventilator being in place the date of event or the day before. 2 The incidence of VAP was reported to be as high as 42%, [3][4][5] but estimates vary substantially depending on different diagnostic scoring systems. 3,6 Also, VAP is associated with substantial morbidity, an increase in mortality, and excess costs.…”
Section: (Received 8 May 2018; Accepted 22 July 2018)mentioning
confidence: 99%
“…1 VAP is defined as pneumonia occurring 48 h following endotracheal intubation with the ventilator being in place the date of event or the day before. 2 The incidence of VAP was reported to be as high as 42%, [3][4][5] but estimates vary substantially depending on different diagnostic scoring systems. 3,6 Also, VAP is associated with substantial morbidity, an increase in mortality, and excess costs.…”
Section: (Received 8 May 2018; Accepted 22 July 2018)mentioning
confidence: 99%
“…Pneumonia is one of the most frequent (6-52%) and serious hospital-acquired infectious complications which occur in critically ill children, and which is treated in the intensive care unit (ICU) [1][2][3][4][5] . Pneumonia is diagnosed in 9-10 cases per 1000 of all hospitalized critically ill patients 1,6 . According to the data of North American and European researchers, the incidence of ventilatorassociated pneumonia (VAP) in patients of multidisciplinary ICU reaches 23.8-32.0% 5 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Nosocomial Infection Surveillance (NNIS) system data, VAP can develop in 6 cases per 1000 patient ventilator days. Thus, the mortality rate in patients with VAP varies from 20-50%, and in some cases, when the etiological factor of this complication is multidrug-resistant agents, may exceed 70% 1,2,[5][6][7][8] . The microbial factor is crucial in causing VA and influences the recovery of patients with this pathology.…”
Section: Introductionmentioning
confidence: 99%
“… 5 This is due to the lack of clinically relevant diagnostic criteria. A recent study by Elliott et al 6 reported a list of diagnostic criteria to establish the VAP incidence in a cohort of 10 Australian ICUs. These criteria evolved through a modified Delphi study and were reviewed by the Quality and Safety Committee of the Australian and New Zealand Intensive Care Society.…”
Section: Introductionmentioning
confidence: 99%
“…These criteria evolved through a modified Delphi study and were reviewed by the Quality and Safety Committee of the Australian and New Zealand Intensive Care Society. 6 …”
Section: Introductionmentioning
confidence: 99%